2022
DOI: 10.1590/0001-3765202220210191
|View full text |Cite
|
Sign up to set email alerts
|

Climate change effects on marginal savannas from central-north Brazil

Abstract: This study estimated the potential effects of climate change on peripheral plant diversity by predicting the distribution of species from Cerrado of Northern Brazil. Ecological niche modeling was used to provide present and future projections of responses in terms of occurrence of ten woody species based on four algorithms and four future climate change scenarios for the year 2050. Potential refuge areas for conservation actions were identifi ed, and evidence of the vulnerability of the fl ora was demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
1
0
0
1
Order By: Relevance
“…Ribeiro et al [52] showed significant impacts of climate change on the environmental suitability of Dipteryx alata Vogel in the Brazilian Cerrado. Similar results have been reported in other studies of plants species from the Cerrado, related to climate change's impacts [52][53][54]. However, despite these studies demonstrating negative effects on the distribution of plants in this biome, Tomaz et al [55] indicated that a medicinal plant species tends to adapt in different environmental conditions, since the distribution of the species tends to decrease in the Atlantic Forest and Caatinga over northeast Brazil.…”
Section: Discussionsupporting
confidence: 65%
“…Ribeiro et al [52] showed significant impacts of climate change on the environmental suitability of Dipteryx alata Vogel in the Brazilian Cerrado. Similar results have been reported in other studies of plants species from the Cerrado, related to climate change's impacts [52][53][54]. However, despite these studies demonstrating negative effects on the distribution of plants in this biome, Tomaz et al [55] indicated that a medicinal plant species tends to adapt in different environmental conditions, since the distribution of the species tends to decrease in the Atlantic Forest and Caatinga over northeast Brazil.…”
Section: Discussionsupporting
confidence: 65%
“…As áreas protegidas do Cerrado desempenham um papel importante na conservação do bioma. Todavia, é imprescindível observar as mudanças no uso e ocupação da terra nessas áreas, visto que, o avanço das atividades agrícolas tem gerado preocupações com a preservação dos habitats naturais e ecossistemas do bioma (CRIVELARI-COSTA et al, 2023).…”
Section: Resiliência Das áReas Protegidas Do Cerradounclassified